Comparison of alexithymia scale and stress coping strategies in patients with methadone and addicts without treatment programs - Mehdi Madanifard (Journal of Birjand University of Medical Sciences, 2017)
Background and Aim: Many studies evaluated addiction and substance abuse treatment. But few studies have investigated alexithymia scale and stress coping strategies in addicted patients. The aims of this study was to compare the alexithymia scale and stress coping strategies in patients with methadone and addiction without treatment programs. Materials and Methods: This was a causal-comparative (ex post facto) research that evaluated using  alexithymia and coping with stress scales. Patients with methadone (n=55) and addiction without treatment programs (n=55) selected by available sampling. Data analysis was performed using independent t-test and descriptive indicators at the significant level of P≤0.05. Results: The average scores on the variables of alexithymia among drug users  127.80±5.2and in patients treated for up to  98.11±3.9 and the average scores ranging coping strategies in people addicted to the  66.2±4 and in patients treated for up to 83.9±6.2 respectively. Independent t-test showed that the mean difference in overall scale and is significant in terms of alexithymia (p <0/001). Also in relation to the overall scale and following scale comparison of the strategies variable was significant mean difference (p <0/001). Conclusion: The results showed that patients with methadone and addiction without treatment programs in the variables of alexithymia and coping strategies are flawed. However, the group was treated through the use of psychological and physical treatment and return relative to health conditions has fewer problems compared to untreated addicted individuals. In addition to the prescription drug treatment programs in these people who pay more attention to psychological interventions are proposed.